Knowledge of Sexual and Reproductive Rights and Experience of Intimate Partner Violence among Female Teachers in South-West Nigeria (African Journal of Biomedical Research, 2023)
Intimate partner violence (IPV) is the most common form of domestic violence in Nigeria and a violation of human rights. Many women are unaware of their sexual and reproductive rights (SRRs) and are unable to exercise them especially in the face of violations to their persons by an intimate partner. There is paucity of information on women’s understanding of their SRRs and how it relates with their experience of IPV in Nigeria. The study was conducted to assess the knowledge, prevalence and pattern of IPV among female secondary school teachers and to determine the association between knowledge of SRRs and experience of IPV in Southwest Nigeria. A cross-sectional study was conducted among 364 teachers using a multi-stage sampling technique. A semi-structured self-administered questionnaire was used to obtain information on respondents’ knowledge of SRRs and experience of IPV. Data was analysed with SPSS version 20 and descriptive statistics were computed. Association between SRRs and experience of IPV was tested using Chi-square at p
Keywords: Sexual health; Reproductive health and rights; Intimate partner violence; Female teachers; Secondary school